Teacher’s Motivation in Community Campus of Rupandehi Districts - Aryal, Sulochana (Devkota Journal of Interdisciplinary Studies, 2025)
This research examines the various factors that affect teacher motivation within community campuses located in the Rupandehi district of Nepal. It places particular focus on elements such as campus facilities, salary and benefits, opportunities for professional development, support from the local community, and the overall work environment. The study aimed to understand how each of these factors shapes teachers’ motivation and to what extent they influence teaching effectiveness. A total of 384 teachers from different community campuses participated in the survey, which was conducted using purposive sampling. The responses were analyzed using descriptive statistics and correlation methods. Results showed that professional development opportunities and strong community involvement had the most significant positive effects on teacher motivation. Teachers pointed to chances for career growth and active participation from parents and community members as the main drivers behind their motivation to perform well. Although infrastructure also played a role, its impact was slightly less strong. Financial incentives such as salary and benefits were found to have a moderate influence, suggesting that money alone may not be enough to sustain long-term motivation. The work environment, including relationships with colleagues and administrators, contributed positively but had the least overall effect. The findings suggest that a balanced approach is necessary to improve teacher motivation – particularly by strengthening professional development programs and encouraging deeper community engagement. These insights are useful for policymakers and educational leaders aiming to support teacher performance and improve educational outcomes across Nepal